2021
DOI: 10.1016/j.eclinm.2020.100665
|View full text |Cite
|
Sign up to set email alerts
|

Prospective association of social circumstance, socioeconomic, lifestyle and mental health factors with subsequent hospitalisation over 6–7 year follow up in people living with HIV

Abstract: Background Predictors of hospitalisation in people with HIV (PLHIV) in the contemporary treatment era are not well understood. Methods This ASTRA sub-study used clinic data linkage and record review to determine occurrence of hospitalisations among 798 PLHIV from baseline questionnaire (February to December 2011) until 1 June 2018. Associations of baseline social circumstance, socioeconomic, lifestyle, mental health, demographic and clinical factors with repeated all-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 37 publications
1
11
0
2
Order By: Relevance
“…Globally, IDU was estimated to cause 4.0% (2.82 million) of disability-adjusted life year due to HIV (DEGENHARDT et al, 2013). On the other hand, socioeconomic disadvantage, adverse lifestyle factors and poorer mental health were strong predictors of hospitalization in IDU (REIN et al, 2020). The authors hypothesize that reduced previous ART taking, inconstant healthcare, and possible socioeconomic circumstances may contribute to mortality in this cohort.…”
Section: Three-year Mortality Predictive Factorsmentioning
confidence: 84%
“…Globally, IDU was estimated to cause 4.0% (2.82 million) of disability-adjusted life year due to HIV (DEGENHARDT et al, 2013). On the other hand, socioeconomic disadvantage, adverse lifestyle factors and poorer mental health were strong predictors of hospitalization in IDU (REIN et al, 2020). The authors hypothesize that reduced previous ART taking, inconstant healthcare, and possible socioeconomic circumstances may contribute to mortality in this cohort.…”
Section: Three-year Mortality Predictive Factorsmentioning
confidence: 84%
“…Overall, 43% of those hospitalised had previous AIDS at baseline (2011) compared to 34% in the whole study population. Our previous findings showed that lower baseline CD4 nadir predicted hospitalisation in this population [ 9 ]. The potential long-lasting effects of immunosuppression on a range of morbidities beyond ADIs specifically [ 17 ] reinforces the importance of timely diagnosis and treatment for HIV.…”
Section: Discussionmentioning
confidence: 95%
“…We previously reported on the association of baseline factors with subsequent all cause hospitalisation [ 9 ]; this report presents a descriptive analysis of the causes of hospitalisation and patient characteristics of those admitted for the most common causes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on table 2 2 articles were assessed for risk of bias using the JBI critical appraisal checklist for a cohort study and the results were: a score of 81.8% (n=2 articles) (Giraud, J.S, et al, 2020, S.M. Rein et al, 2021). Based on the identification in table 1, 20 articles were assessed for risk of bias using the JBI critical assessment checklist for the design of Cross-Sectional Study, Cohort Study, Prevalence Study, and QuasiExperimental Study.…”
Section: Resultsmentioning
confidence: 99%